2023
DOI: 10.1007/s00403-023-02613-6
|View full text |Cite|
|
Sign up to set email alerts
|

Routine imaging guided by a 31-gene expression profile assay results in earlier detection of melanoma with decreased metastatic tumor burden compared to patients without surveillance imaging studies

Abstract: Patients with early-stage disease typically have a good prognosis, but still have a risk of recurrence, even with negative sentinel lymph node biopsy (SLNB). This study explores the utility of routine imaging to detect metastases in patients with negative SLNB but high-risk 31 gene expression profile (31-GEP) scores. We retrospectively identified melanoma patients with negative SLNBs. Patients with high-risk GEP results were placed in the experimental group and patients without GEP testing were placed in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“… 28 The clinical impact of the prognostic 31-GEP has been previously demonstrated in multiple clinical utility studies, 27 , 29 and a recent study found that sentinel lymph node biopsy (SLNB)-negative patients with high-risk 31-GEP results who received routine imaging surveillance had recurrence detected earlier with lower tumor burden at recurrence detection and had higher survival rates after recurrence than those who did not have 31-GEP testing and routine imaging. 30 Thus, although the current analysis cannot conclusively determine the mechanism whereby 31-GEP testing is associated with better outcomes, one potential possibility is that clinical action in response to this specific molecular prognostic test supports patient survival. However, a limitation of the SEER data set is that data regarding treatment, surveillance, or other management actions are not available.…”
Section: Discussionmentioning
confidence: 84%
“… 28 The clinical impact of the prognostic 31-GEP has been previously demonstrated in multiple clinical utility studies, 27 , 29 and a recent study found that sentinel lymph node biopsy (SLNB)-negative patients with high-risk 31-GEP results who received routine imaging surveillance had recurrence detected earlier with lower tumor burden at recurrence detection and had higher survival rates after recurrence than those who did not have 31-GEP testing and routine imaging. 30 Thus, although the current analysis cannot conclusively determine the mechanism whereby 31-GEP testing is associated with better outcomes, one potential possibility is that clinical action in response to this specific molecular prognostic test supports patient survival. However, a limitation of the SEER data set is that data regarding treatment, surveillance, or other management actions are not available.…”
Section: Discussionmentioning
confidence: 84%
“… 6 , 7 A recent study revealed that non‐randomized Stage I–II patients with high‐risk GEP test results, when subjected to scheduled imaging, had earlier detection of recurrences and lower tumor burden than those without GEP testing or scheduled imaging. 8 On the other hand, it is not clear whether GEP testing provides greater prognostic accuracy than AJCC staging across all melanoma stages, and the optimal timing of adjuvant therapy for unresectable metastatic disease is unknown. Thus, it remains unclear if and how patients should be selected for adjuvant therapy based on GEP test results.…”
Section: Introductionmentioning
confidence: 99%